Effect of copper nanoparticles on the flexural strength of heat polymerized acrylic resin - Sriram Venkatachalapathy; Gopi N Chander; J Ramesh Reddy; Balasubramaniam Muthukumar (Wolters Kluwer Medknow Publications, 2023)
The aim of this study was to investigate the flexural strength of heat cure acrylic resin reinforced with varying concentration copper nanoparticles. The study followed ISO 20795-1-2013 guidelines for estimating the flexural strength. Hundred samples of heat cure acrylic resin of dimension were fabricated. The study had five groups and each group had 20 samples. The samples were grouped as per the concentration of copper (Cu) nanoparticles in acrylic. Three-point bending flexural strength was evaluated with universal testing machine. The load was directed at the midpoint of the sample at a cross-sectional speed of 5 mm/min. The fractured load was recorded and flexural strength was estimated. The data were statistically analyzed with analysis of variance and the post hoc test. The results displayed improved flexural strength in lower Cu concentrations. The increase in flexural strength was observed in 1% (78.38 MPa), 2% (73.08 MPa), and 3% (73.08 MPa) of Cu nanoparticles and it decreased beyond 3% increase in Cu nanoparticles. The tests were statistically insignificant (P <.05). The results concluded that the optimal concentration of Cu nanoparticles to be reinforced with heat cure PMMA is 1 gm. The flexural strength decreased with an increase in concentration of Cu nanoparticles.